STRATEGI PENGUATAN BUDAYA MUTU DALAM PENJAMINAN MUTU INTERNAL PERGURUAN TINGGI: SYSTEMATIC LITERATURE REVIEW - Tomy Sun Siagian; Dhea Agusty Ningrum; Taufiq Hidayah; R. Sabrina (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Higher education institutions face increasing demands to enhance educational quality, accountability, and global competitiveness. However, quality assurance initiatives often fail to foster a strong quality culture and are therefore frequently perceived as merely administrative procedures. This study aims to identify strategies recommended in the literature to strengthen quality culture through internal quality assurance (IQA) systems in higher education institutions. The method employed is a Systematic Literature Review (SLR), involving a comprehensive search of articles across reputable databases using Boolean strings related to quality culture, higher education, and internal quality assurance. This process is followed by screening based on inclusion–exclusion criteria and thematic analysis of the selected studies. Out of an initial 149 articles, only 5 met the eligibility criteria and were included in the final analysis to synthesize the findings. The results reveal four key strategies for strengthening quality culture: (1) reinforcing quality-oriented leadership, (2) establishing systematic governance of IQA, (3) fostering stakeholder engagement, and (4) developing human resource competencies through innovation and continuous improvement. Therefore, a sustainable quality culture can be established when IQA is not merely positioned as a compliance mechanism, but rather as a framework for organizational transformation that is implemented collaboratively and consistently across all levels of higher education institutions. Keywords: Internal Quality Assurance; Higher Education; Quality System; Continuous Improvement; Stakeholder Engagement   Abstrak: Perguruan tinggi menghadapi tuntutan peningkatan mutu pendidikan, akuntabilitas, dan daya saing global, namun upaya penjaminan mutu sering kali belum berhasil menumbuhkan budaya mutu yang kuat sehingga hanya dipandang sebagai prosedur administratif semata. Penelitian ini bertujuan mengidentifikasi strategi yang direkomendasikan dalam literatur untuk memperkuat budaya mutu melalui sistem penjaminan mutu internal di perguruan tinggi. Metode yang digunakan adalah Systematic Literature Review (SLR) dengan pencarian artikel pada berbagai database bereputasi menggunakan Boolean string terkait quality culture, higher education, dan internal quality assurance, dilanjutkan dengan proses screening berbasis kriteria inklusi–eksklusi, serta analisis tematik terhadap artikel yang lolos seleksi . Dari 149 artikel awal, hanya 5 artikel yang memenuhi kriteria dan dianalisis sebagai dasar penyusunan sintesis temuan. Hasil menunjukkan empat strategi utama dalam penguatan budaya mutu, yaitu penguatan kepemimpinan mutu, tata kelola SPMI yang sistematis, keterlibatan pemangku kepentingan, dan pengembangan kompetensi SDM melalui inovasi serta continuous improvement. Dengan demikian, budaya mutu akan terbangun ketika IQA tidak hanya menjadi alat kepatuhan, tetapi menjadi kerangka transformasi organisasi yang dijalankan secara kolaboratif dan konsisten di seluruh level perguruan tinggi. Kata Kunci: Penjaminan Mutu Internal; Pendidikan Tinggi; Sistem Mutu; Continuous Improvement; Stakeholder Engagement